2016
DOI: 10.1189/jlb.5a1215-580r
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-reactive immune cells protect against metastatic tumor and induce immunoediting of indolent but not quiescent tumor cells

Abstract: Quiescent, but not indolent, dormant tumor cells are resistant to immunoediting, and best targets for immunotherapy of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 22 publications
(34 reference statements)
1
53
0
Order By: Relevance
“…We have also reported that the use of Aza combined with the immune modulatory lenalidomide induced the expression of CTAs within tumor cells, and generated CTA-specific immune responses in patients with multiple myeloma [64]. Similar results were observed in a mouse model of experimental metastatic breast cancer [65]. Therefore, Dec is an attractive candidate as a neoadjuvant immune modulator when combined with immunotherapy.…”
Section: Epigenetic Targeting Of Tumor Cells For Immune Modulationmentioning
confidence: 62%
See 1 more Smart Citation
“…We have also reported that the use of Aza combined with the immune modulatory lenalidomide induced the expression of CTAs within tumor cells, and generated CTA-specific immune responses in patients with multiple myeloma [64]. Similar results were observed in a mouse model of experimental metastatic breast cancer [65]. Therefore, Dec is an attractive candidate as a neoadjuvant immune modulator when combined with immunotherapy.…”
Section: Epigenetic Targeting Of Tumor Cells For Immune Modulationmentioning
confidence: 62%
“…It has been reported that dormant tumor cells, while become refractory to chemotherapy, remain susceptible to immunotherapy [65]. Therefore, the next generation immunotherapeutics are expected to be highly effective against cancer, when combined immune modulatory compounds.…”
Section: Control Of Cell Cycle Progression Prior To Immunotherapymentioning
confidence: 99%
“…Examination of genetic background and intercellular signaling may unveil regulatory biomarkers that regard GOQ-2 and GOQ-3. Tumor invasion is variably dynamic and thought to occur by EMT processes in some contexts [204,[219][220][221][222][223]. However, the EMT is not the only program for tumor invasion.…”
Section: Molecular Connections Between Lc and Pcmentioning
confidence: 99%
“…Genetic background across the tumor-stromal axis is the blueprint for cancer behavior [219,251,292]. Inquiries might include: pleiotropic pathways, genomic reconfigurations (e.g., aneuploidy, copy number variations, microinsertions, microdeletions, and translocations), genetic mutations (e.g., promoter, intronic, exonic, and splicing mutations), epigenetic alterations (e.g., de-, hyper-, and hypo-methylation, and deacetylation), epistatic genes and their interactions, diversified miR expression, EMT and non-EMT drivers of tumor invasion, autophagy and metabolism, ECM interactions, exosome-content dispersion, inflammatory mediators, stromal and ECM mediators, and angiogenic and lymphangiogenic mediators.…”
Section: Pan-cancer Analysismentioning
confidence: 99%
“…Masoud Manjili of VCU Massey Cancer Center is a tumor immunologist whose research program is focused on immunotherapy of breast cancer and targeting tumor dormancy while overcoming immune suppressor cells (Manjili, 2014;Payne et al, 2016). In their review, Manjili and Butler discuss the poorly understood concept of tumor cell dormancy in the context of immune-mediated maintenance, as well as escape and subsequent recurrence.…”
Section: Immune Regulatory Function Of Tregsmentioning
confidence: 99%